Study of the Interaction Effect Between Parsley Petroselinum crispum and Cadmium on Lipid Profile, Lipid Peroxidation and Catalase Activity of Albino Mice Males’ Liver and Kidney - Yousuf, Huda (Iraqi Journal of Science, 2023)
This study was designed to investigate the effect of different cadmium concentrations on albino mice males’ oxidative balance through lipid profile, malondialdehyde (MDA) concentration and catalase (CAT) activity estimation in liver and kidney. Parsley Petroselinum crispum was chosen to detect its effect as a natural antioxidant.Five groups of albino mice males (10 mice each) were treated with (0.0, 0.25, 0.5, 0.75 and 7.5) mg Cd/kg b.w. orally by using gavages needle for 60 days according to 5 days/week protocol, another five mice groups were treated with the same cadmium concentrations mentioned above and 0.1 ml of parsley Petroselinum crispum juice.The results showed an adverse effect of cadmium on mice oxidative balance, while parsley showed an effective antioxidant effect which was revealed through lipid profile protection, MDA concentrations decrease and CAT activity increase.